Pengaruh Sektor Pariwisata Terhadap Pendapatan Asli Daerah (PAD) Di Kabupaten Alor Provinsi Nusa Tenggara Timur - Conbaiamore Beri; Nikson Tameno; Aldarine Molidya (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This study aims to analyze: 1) the effect of the number of tourists on local original income in Alor Regency, 2) the influence of tourist attractions on local original income in Alor Regency, 3) the effect of hotel occupancy rate on local original income in Alor Regency, 4) The effect of the number of tourists, tourist attractions and hotel occupancy rates in Alor Regency. The type of research used in this study is quantitative descriptive research. Data types and sources use a quantitative approach with secondary data in the form of time series data with an observation period of 2011-2021. The results showed that: hypothesis First, a positive and significant influence between the number of tourists on local original income in Alor Regency as shown by a coefficient value of -894960.9, Because the calculated t value is -0.332076 < t table 1.943 with a significant value of 0.7511 > α = 0.05, then reject Ho and accept Ha. This means that if the number of tourists increases by one percent, it affects the original income of the Alor Regency area by 0.332076.Second, tourist attractions have a significant and positive effect on the original income of the region in Alor Regency, which is shown by the value of the coefficient of 4.59E + 08. The value of this coefficient is significant because the calculated value of 0.607077 < ttable 1.943 and significant 0.5660 >α = 0.05 then reject H0 and accept Ha. This means that if the tourist attraction increases by one percent, the original income of the Alorakan Regency area increases by 0.607077. Third, the hotel occupancy rate does not significantly affect the local original income, which is indicated by the coefficient value of 6.44E+09. The value of this coefficient is not significant because the calculated value, 0.624792 > ttable of 1.943 with a significant value of 0.5551 >αα = 0.05 then reject H0 and accept Ha. This means that there is no influence between hotel occupancy rates on the original income of Alor Regency. Fourth, the number of tourists, tourist attractions and hotel occupancy rates simultaneously have a positive and significant effect on the original income of the Alor Regency area, which is indicated by the value of Fcalculate 53.71137 > Ftable 3.326 and a significant value of 0.038976<α = 0.05, then reject H0 and accept Ha. This means that the number of tourists, attractions and hotel occupancy rates can affect the variance in local original income by 54% and the rest is explained by other variables.